Sleep Quality and Screen Time as The Most Influential Factor of Computer Vision Syndrome - Dhafira, Farhana; Prihatningtias, Riski; Nugroho, Trilaksana; Maharani, Maharani (Jurnal Promosi Kesehatan Indonesia, 2023)
Background: Since the Covid-19 Pandemic hit Indonesia, college students have had many eye health complaints; one is Computer Vision Syndrome (CVS). Factors that can increase the risk of CVS are decreased sleep quality, high computer/laptop use duration, and a non-ergonomic position. This study aimed to prove the relationship between sleep quality, visibility, and screen time on the incidence of CVS in medical students of Diponegoro University.Method: This cross-sectional study, including 147 medical students was conducted using primary data from questionnaires of Wendy Strouse Watt, Thomas H Murphy, Hospitality Eye Care Center, and vsp.com to gain data on respondent identity, visibility, and screen time. Sleep quality data were taken from the PSQI and CVS data through the CVS-Q questionnaire. Chi-square, Mann-Whittney, and logistic regression of multivariate analysis were used to analyze the data.Results: From 147 subjects, 108 were CVS (73.5%), and 39 were Non-CVS (26.5%). Variables of sleep quality and screen time (total) showed a significant relationship with CVS, which had p-values of p=0.001 and p=0.009 (p<0.05). As for the visibility to CVS, there was no relationship with p=0.863. In the multivariate test, sleep quality (p=0.000; ExpB=4.342) and total screen time (p=0.006; ExpB=3.913) were the most influential variables. The results showed that Computer Vision Syndrome is ubiquitous among Diponegoro University's final-year medical students. Sleep quality and total screen time can increase the risk of CVS by four times. This study also shows that CVS still appears in the post-pandemic era.